Implementation of curriculum models in ICT subjects at SD Al-Hidayah Majalengka - Abi Yasid Al’majid (Himpunan Pengembang Kurikulum Indonesia, 2025)
Information and Communication Technology (ICT) learning in elementary school is a crucial foundation for equipping students with digital literacy from an early age. This study aims to identify how ICT learning is implemented at SD Al-Hidayah, particularly in terms of instructional structure, learning materials, teaching approaches, and alignment with applicable Basic Competencies. The research is motivated by the need to understand how ICT education is applied in practice as a response to the development of digital technologies and 21st-century education demands. A descriptive qualitative method was used, employing in-depth interviews, document analysis, and participatory observation as data collection techniques. The results show that ICT learning at the school is systematically implemented through instructional tools that refer to achievement indicators, contextually relevant materials, and hands-on learning approaches that encourage student engagement. However, challenges such as limited facilities and the need for further teacher training were identified. These findings highlight the importance of enhancing teacher competence and strengthening infrastructure as strategic efforts to optimize ICT learning at the elementary level. Abstrak Pembelajaran Teknologi Informasi dan Komunikasi (TIK) di jenjang Sekolah Dasar menjadi fondasi penting dalam membekali peserta didik dengan literasi digital sejak dini. Penelitian ini bertujuan untuk mengidentifikasi pelaksanaan pembelajaran TIK di SD Al-Hidayah, khususnya dari aspek struktur ajar, materi pembelajaran, pendekatan guru, serta kesesuaiannya dengan Kompetensi Dasar yang berlaku. Penelitian ini dilatarbelakangi oleh kebutuhan untuk memahami bagaimana pembelajaran TIK diimplementasikan di lapangan sebagai respons terhadap perkembangan teknologi digital dan tuntutan pendidikan abad 21. Metode yang digunakan adalah penelitian kualitatif deskriptif, dengan teknik pengumpulan data berupa wawancara mendalam, analisis dokumen, dan observasi partisipatif. Hasil penelitian menunjukkan bahwa pembelajaran TIK di sekolah tersebut telah dilaksanakan secara sistematis dengan perangkat ajar yang mengacu pada indikator keberhasilan, materi pembelajaran yang kontekstual, serta pendekatan praktik langsung yang mendorong keterlibatan aktif peserta didik. Meskipun demikian, beberapa kendala seperti keterbatasan fasilitas dan kebutuhan pelatihan guru masih ditemukan. Temuan ini menekankan pentingnya peningkatan kompetensi pendidik dan penguatan infrastruktur sebagai langkah strategis dalam optimalisasi pembelajaran TIK di tingkat sekolah dasar. Kata Kunci: implementasi pembelajaran; pengembangan kurikulum; sekolah dasar; teknologi informasi dan komunikasi